2015
DOI: 10.1213/ane.0000000000000743
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Adding a Background Infusion to Patient-Controlled Epidural Labor Analgesia on Labor, Maternal, and Neonatal Outcomes

Abstract: On the basis of current evidence, no conclusion can be drawn regarding the risks or benefits of adding a continuous background infusion to PCEA compared with PCEA-only epidural labor analgesia. Further high-quality studies involving a sufficient number of patients are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 17 publications
2
25
0
3
Order By: Relevance
“…Although these estimates are based on publications by the Cochrane Collaboration, others have also found that publications in obstetrics and gynaecology journals comprise a large portion of systematic reviews available [ 36 ]. As such, it should come as no surprise that systematic reviews and meta-analysis in Pregnancy and Childbirth have shaped essential clinical decisions, such as timing of corticosteroid administration for women at risk for preterm birth [ 32 ], methods of labour induction [ 37 ], approaches to intrapartum anaesthesia [ 38 , 39 ], interventions for postpartum complications [ 40 ] and more [ 41 45 ]. With increased availability and use of systematic reviews and meta-analyses in making clinical decisions, it is essential that the quality of these works be maintained at the highest level.…”
Section: Discussionmentioning
confidence: 99%
“…Although these estimates are based on publications by the Cochrane Collaboration, others have also found that publications in obstetrics and gynaecology journals comprise a large portion of systematic reviews available [ 36 ]. As such, it should come as no surprise that systematic reviews and meta-analysis in Pregnancy and Childbirth have shaped essential clinical decisions, such as timing of corticosteroid administration for women at risk for preterm birth [ 32 ], methods of labour induction [ 37 ], approaches to intrapartum anaesthesia [ 38 , 39 ], interventions for postpartum complications [ 40 ] and more [ 41 45 ]. With increased availability and use of systematic reviews and meta-analyses in making clinical decisions, it is essential that the quality of these works be maintained at the highest level.…”
Section: Discussionmentioning
confidence: 99%
“…The intrathecal block might cut off the afferent impulse of the muscular spindle, which may reduce the stretch reflex of the abdominals and pelvic floor muscles whose muscle force and muscular tension will be correspondingly weakened. This all results in a weakening of the total labor force, therefore prolonging the second and third stages of labor and causing more postpartum bleeding [14] (Tables 8 and 9). The research by Wood shows that once the air-blood that covers PH, PO2, and BE is dropped, PCO2 increases substantially [15] (Table 10).…”
Section: Applied In Painless Labormentioning
confidence: 99%
“…Most North American and European institutions undertake standard labor epidural analgesic regimens including local anesthetics combined with an opioid given via CEI with or without PCEA boluses. Although compared with non-neuraxial analgesia, CEI with or without PCEA has better analgesic effects, as high doses of local anesthetic doses lead to profound motor blockade [ 5 ]. There is a decreased ability to move, decreased pelvic floor muscle tension, and inability to hold down during the second stage of labor.…”
Section: Introductionmentioning
confidence: 99%